2014
DOI: 10.1371/journal.pone.0098458
|View full text |Cite
|
Sign up to set email alerts
|

Progastrin Represses the Alternative Activation of Human Macrophages and Modulates Their Influence on Colon Cancer Epithelial Cells

Abstract: Macrophage infiltration is a negative prognostic factor for most cancers but gastrointestinal tumors seem to be an exception. The effect of macrophages on cancer progression depends on their phenotype, which may vary between M1 (pro-inflammatory, defensive) to M2 (tolerogenic, pro-tumoral). Gastrointestinal cancers often become an ectopic source of gastrins and macrophages present receptors for these peptides. The aim of the present study is to analyze whether gastrins can affect the pattern of macrophage infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…CD68 + TAMs had no prognostic value in predicting the outcome of surgically treated ICC patients, which may be attributed to the inability of CD68 to distinguish between M1 and M2 subsets. This was consistent with previous studies in HCC, colon cancer and gastric cancer (Dong et al, 2016;Hernandez et al, 2014;Zhang et al, 2015). Therefore, CD86 and CD206 immunostaining were further examined to distinguish between M1 and M2 subtypes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…CD68 + TAMs had no prognostic value in predicting the outcome of surgically treated ICC patients, which may be attributed to the inability of CD68 to distinguish between M1 and M2 subsets. This was consistent with previous studies in HCC, colon cancer and gastric cancer (Dong et al, 2016;Hernandez et al, 2014;Zhang et al, 2015). Therefore, CD86 and CD206 immunostaining were further examined to distinguish between M1 and M2 subtypes.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, compelling evidence showed that M1 subtype macrophages expressed abundant CD86, CD38, Gpr18, Fpr2 and tumor necrosis factor a, whereas M2 subtype macrophages expressed high levels of CD206, CD163, Egr2 and c-Myc (Biswas & Mantovani, 2010;Olsson et al, 2015;Jablonski et al, 2015). Recent studies found that M1 subtype macrophages possessed high levels of CD86, while M2 subtype macrophages expressed high levels of CD206 in human gastrointestinal tumors tissues (Hernandez et al, 2014;Zhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This may attribute to functional counterbalance regulated by M1 and M2 macrophages. Previous studies in HCC, colon cancer and gastric cancer implied that the abundance of CD68 + TAMs infiltrated in tumor tissue was not associated with patient prognosis after curative cancer tissue resection [ 24 , 25 , 26 ]. However, other research reported that CD68 + TAMs in tumor stroma was an independent prognostic factor for poor OS and TTR in breast cancer, cholangiocarcinoma and Hodgkin lymphoma [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of our data that challenge the current theory regarding the prognostic role of CD163+ TAMs has not been entirely elucidated. However, several authors have argued that M2 macrophages have less deleterious effects in CRCs, which is attributed to the unique intestinal environment with numerous colonizing micro-organisms [ 18 , 35 , 36 ]. This less hazardous effect of M2 macrophages can be applied to GCs considering the fact that the vast majority of GCs arise in the stomach infected with Helicobacter pylori and that GCs have molecular mechanisms of carcinogenesis in common with CRCs.…”
Section: Discussionmentioning
confidence: 99%